Front-Line Therapy for Elderly Chronic Lymphocytic Leukemia Patients: Bendamustine Plus Rituximab or Chlorambucil Plus Rituximab? Real-Life Retrospective Multicenter Study in the Lazio Region - Autore, Francesco; Innocenti, Idanna; Corrente, Francesco; Del Principe, Maria Ilaria; Rosati, Serena; Falcucci, Paolo; Fresa, Alberto; Conte, Esmeralda; Limongiello, Maria Assunta; Renzi, Daniela; De Padua, Laura; Andriani, Alessandro; et al. (Frontiers in Oncology, 2020)
Previous studies investigated efficacy and safety of Bendamustine (B) vs Chlorambucil (Chl) associated with Rituximab (R) in Fludarabine-ineligible patients with treated and untreated CLL. We conducted a retrospective multicenter study in the Lazio region to further evaluate and compare efficacy and toxicity of Chl-R and B-R regimen in CLL patients over the age of 65. We enrolled 192 untreated CLL patients, 111 treated with B-R and 81 with Chl-R. The ORR (93.6% in B-R and 86.5% in Chl-R) was not statistically different between the two groups, such as PFS, TTR and OS. B-R group showed a higher haematological (p=0.007) and extra-haematological (p=0.008) toxicity. When comparing toxicities according to age, we noted that extra-haematological toxicity was higher in patients over the age of 75 who were treated with B-R than those treated with Chl-R (p=0.03). This retrospective study confirms the feasibility of B-R and Chl-R in elderly untreated CLL patients. Currently, patients who are over 75 and unfit are usually treated with Chl-R. This scheme allows to achieve the same ORR, PFS, TTR and OS when compared with B-R because of haematological and extra-haematological toxicities due to B, in which a greater dose reduction has been shown in comparison to Chl.